ANALISIS RANTAI NILAI (VALUE CHAIN) TERHADAP PRODUKSI PIRING ROTAN ORONG TELU-SUMBAWA - Nurul Hudaningsih (JURNAL INDUSTRI DAN TEKNOLOGI SAMAWA, 2020)
Some of the people in Orong Telu District have livelihoods in agriculture,plantations etc., one of which is the rattan raw material supply industry. One small industryrattan processing is a rattan industrial center such as the one in Orong Telu District. CenterThis rattan industry is the largest in Sumbawa Regency. Rattan processing hereproduced by the cutting system and the traditional system. Rattan production in Orong Telu Districtit has been marketed outside the district of Sumbawa with an average production capacity10-15 tonnes per week. This study aims to see the development of rattan processing inRattan Industry Center in Orong Telu District, analyzes the value chain of the industryyellow rattan in Orong Telu District, and determine the strategy for strengthening the rattan industry.